Scrutiny of Bio-Gas from Kitchen Waste by Means of Anaerobic Digester - M. Sivaprakash; S. R. Raj Kumar; C. Dhayananth Jegan; I. P. Rakhesh (Cutting Edge Research in Biology Vol. 7, 2023)
The enhancement of the energy sectors is the focus of research projects everywhere in the world. Because energy will become increasingly important in all aspects of human life in the future years. Fossil fuels provide the foundation for the generation of conventional energy. Researchers concentrate on finding ways to switch from using fossil fuels to producing energy from renewable sources. One method of generating energy is using kitchen garbage to produce biogas. Anaerobic digestion is economical and environmentally friendly. Methane and carbon dioxide are the two main components of the biogas produced by anaerobic digestion of kitchen trash. Using sodium hydroxide helps the anaerobic digestion process retain its alkalinity (pH = 7). To assess this method of generating energy on our campus, Stella Mary’s College of Engineering, Nagercoil, Kanyakumari District, Tamil Nadu, India, a model is created with basic design and implement in our campus and get analysed.